2013
DOI: 10.3233/jid-2013-0004
|View full text |Cite
|
Sign up to set email alerts
|

Managing Cognitive Load in Introductory Programming Courses: A Cognitive Aware Scaffolding Tool

Abstract: Research on techniques for teaching computer programming to novice learners has suggested that introducing programming concepts and theories is extremely difficult because the learners have to assimilate syntactical methods of the programming language as well as their interface to the programming world. Computer programming for the novice requires the understanding of a variety of different areas such as logic and mathematical concepts, syntax, the language interface, algorithms, flowcharts, and pseudocode ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
21
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 63 publications
(21 citation statements)
references
References 16 publications
0
21
0
Order By: Relevance
“…Researchers advocated that it is difficult to reduce cognitive load during the learning process of programming (Mead et al 2006;Renkl and Atkinson 2003;Stachel et al 2013). Mason, Cooper, and Wilks (2015) documented that some of the programming environments may be complex and cause an adverse impact on learners' focus of attention and overloading cognitive resources for learning.…”
Section: Cognitive Load In Programmingmentioning
confidence: 99%
“…Researchers advocated that it is difficult to reduce cognitive load during the learning process of programming (Mead et al 2006;Renkl and Atkinson 2003;Stachel et al 2013). Mason, Cooper, and Wilks (2015) documented that some of the programming environments may be complex and cause an adverse impact on learners' focus of attention and overloading cognitive resources for learning.…”
Section: Cognitive Load In Programmingmentioning
confidence: 99%
“…Sweller (2008) claimed that instructional strategies and activities, which include scaffolding systems, have a big influence on cognitive load. Directly linked to the current study, Stachel et al (2013) provided scaffolding tools to the programming learners in their experimental research, and results showed that the tool decreased their cognitive load and made a modest contribution to course scores. Similarly, Salleh et al (2018) generated a scaffolding tool based on cognitive load theory and decreased cognitive load of novice learners.…”
Section: Discussionmentioning
confidence: 88%
“…The reason for these meaningful negative relationships (in favor of low difficulty level questions) may be due to that programming requires keeping various information at different levels in the working memory. This information is stated as syntactic details, mental models for problem-solving and specifying the solution for problems (Balzert, 2004;Rist, 1995;Stachel et al, 2013). As the level of difficulty increases, the load on the working memory also increases, considering the requirements of programming.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…No single teaching approach seems to benefit all students. A proportion of students can readily comprehend a concept, such as repetition, as written in a textual language, for example Java, but a significant group will always be frustrated and require other forms of illustration of the concept which present less or differing cognitive load (Stachel et al, 2013). This paper reports an investigation into the efficacy of a blocks based language for learning programming.…”
Section: Introductionmentioning
confidence: 99%